Cellulose acetate tablet, and gold recovery method and concentration method using same

By using cellulose acetate sheets that control acetyl substitution degree and average spatial velocity as filler for the gold recovery column, the problems of low gold recovery efficiency and poor liquidity in the prior art are solved, and the effect of efficient and selective recovery of gold is achieved.

CN120112562APending Publication Date: 2025-06-06DAICEL CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202380075028.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-31
Filing Date
2023-10-31
Publication Date
2025-06-06

AI Technical Summary

Technical Problem

The prior art has problems in the gold recovery process that low selective separation efficiency, high energy consumption cost of repeated purification, and poor liquidity throughput of the packed column.

Method used

Cellulose acetate sheets are used as filler to ensure high-pass liquidity and selective adsorption of gold ions by controlling their acetyl substitution degree and average spatial velocity.

Benefits of technology

It realizes efficient and selective recovery of gold from the gold-containing solution, reduces energy consumption, and improves the liquidity of the gold recovery column.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005373725250000311
    Figure BDA0005373725250000311
  • Figure BDA0005373725250000312
    Figure BDA0005373725250000312
  • Figure BDA0005373725250000322
    Figure BDA0005373725250000322
Patent Text Reader

Abstract

A cellulose acetate tablet which is composed of cellulose acetate having a degree of acetyl substitution of 0.80-2.90, and which has an average spatial velocity (SV), as determined by a prescribed method, of more than 1.0 h <-1 > and 120 h <-1 > or less. The gold recovery method comprises the following steps: filling a cylindrical container with the cellulose acetate sheet to form a packed column; and introducing a liquid containing gold ions into the packed column, so that the gold ions are adsorbed on the cellulose acetate sheet.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a cellulose acetate sheet. Specifically, the present disclosure relates to a cellulose acetate sheet filled in a gold recovery column, a gold recovery column filled with the cellulose acetate sheet, and a gold recovery method using the column. Background Art

[0002] In recent years, many electrical / electronic devices such as mobile phones have been used and discarded. Various metals such as precious metals and rare metals are used in these electrical / electronic devices. Therefore, discarded electrical / electronic devices are called "urban mines" for collecting precious metals and have attracted attention. In particular, gold (Au) is a material for bonding wires that connect electrodes of IC chips to lead frames, and is used in large quantities. Therefore, a technology for efficiently recovering gold from urban mines is sought.

[0003] For example, the following technology is known: electronic components containing gold are crushed, immersed in a mixture of nitric acid and hydrochloric acid, extract and dissolve precious metals, and after filtering as needed, a reducing agent is added to the aqua regia solution to separate low-purity crude gold. The crude gold also contains metals other than gold and insoluble substances that cannot be removed by filtering as impurities. In order to recover gold with a purity of 99.99% (four nines) or more, it is necessary to repeat the process of purifying the separated crude gold many times, which has the problem of consuming energy costs.

[0004] Japanese Patent Application Laid-Open No. 1-111453 (Patent Document 1) discloses a technique for separating the rare metal by passing a solution containing a rare metal such as samarium through a column equipped with a filter filled with a pellet-shaped ion exchange resin.

[0005] Japanese Patent Application Laid-Open No. 2014-109064 (Patent Document 2) proposes a metal recovery method, which uses a carboxylic acid ester of a polysaccharide as a metal capture material to capture metals in a solution. In Patent Document 2, powdered or fibrous cellulose acetate is added as a metal capture agent to a solution containing gold ions and stirred to adsorb gold ions to the cellulose acetate.

[0006] Japanese Patent Application Laid-Open No. 2017-052961 (Patent Document 3) discloses a cellulose acetate powder, which is composed of cellulose acetate having an acetylation degree of 53% to 56% and a viscosity of 30 to 200 mPa·s, a cumulative pore volume of 0.2 ml / g or more, a ratio of particles having a particle size of 500 μm or more of 40% or less, and a repose angle of 51° or less. The cellulose acetate powder is produced by pulverizing a cellulose acetate sheet.

[0007] Japanese Patent Application Laid-Open No. 2020-204002 (Patent Document 4) discloses a cellulose acetate sheet, which is composed of cellulose acetate having a xylose molar content of 0.5 mol% or more and 1.0 mol% or less, and has an absorbance hue of 0.47 cm -1 The water content is less than 2% by mass and the specific surface area is 9m 2 International Publication No. 2016 / 020952 (Patent Document 5) discloses a cellulose acetate sheet having an average acetylation degree of 60.0% to 61.5%, a viscosity average polymerization degree of 360 to 440, and a filterability of 100 or less.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent Application Laid-Open No. 1-111453

[0011] Patent Document 2: Japanese Patent Application Publication No. 2014-109064

[0012] Patent Document 3: Japanese Patent Application Publication No. 2017-052961

[0013] Patent Document 4: Japanese Patent Application Publication No. 2020-204002

[0014] Patent Document 5: International Publication No. 2016 / 020952 Summary of the invention

[0015] Problems to be solved by the invention

[0016] Patent Document 1 does not describe a technique for selectively separating only gold. In addition, in the technique of Patent Document 1, a phenol compound having a carboxyl group, a compound having a phenolic hydroxyl group, and an aldehyde compound need to be subjected to polycondensation reaction under alkaline conditions by a known method, which is complicated and has a low recovery efficiency.

[0017] Patent document 2 is an intermittent adsorption operation, and there are problems such as a decrease in adsorption efficiency as the gold ion concentration of the solution containing gold ions decreases. In addition, if the process cost in industry is taken into consideration, the gold recovery technology using a packed column is advantageous. However, according to the opinions of the inventors of the present disclosure, the pressure loss when passing liquid through a column filled with powdered cellulose acetate is too large, and sometimes the liquid passing speed is low or liquid cannot be passed. In addition, cellulose acetate in the form of long fiber bundles is difficult to be uniformly filled into the column, and due to local over-dense filling, the liquid passing speed is sometimes low or liquid cannot be passed.

[0018] In order to efficiently recover gold from a gold-containing solution, a filler that has excellent liquid permeability when filled into a column and can selectively adsorb gold is required. Although Patent Document 2 discloses the selective adsorption ability of cellulose acetate for gold, as mentioned above, cellulose acetate in powder form and long fiber bundle form is difficult to use as a column filler. In Patent Documents 3-5, sheet-shaped cellulose acetate is disclosed as another solution. However, all of the technologies are proposed for the purpose of molding cellulose acetate sheets, and the shape and size of the cellulose acetate sheet itself are not specified.

[0019] A cellulose acetate sheet that can be uniformly filled in a column and can exhibit excellent liquid permeability has not yet been proposed. The present disclosure aims to provide a cellulose acetate sheet that can be used as a filler for a column for gold adsorption (recovery). Another object of the present disclosure is to provide a method for selectively adsorbing and recovering gold from a gold-containing solution, particularly a gold-containing solution obtained by dissolving gold from processing scraps of electronic parts and decorative items, waste catalysts, etc. using aqua regia.

[0020] Solutions for solving problems

[0021] The cellulose acetate sheet of the present disclosure is composed of cellulose acetate having an acetyl substitution degree of 0.80 or more and 2.90 or less. The average space velocity SV of the cellulose acetate sheet exceeds 1.0 h -1 And 120h -1 The average space velocity SV is obtained by placing a column (inner diameter 10 mm) filled with cellulose acetate sheets at a height of 2.0 cm from the bottom in a vertical direction, injecting a 2.0 mol / l hydrochloric acid solution (temperature 20°C ± 5°C) from the upper surface of the column, and allowing it to flow down in the column under atmospheric pressure. The amount of liquid flowing out from the lower surface per unit time (m 3 / h) divided by the volume of the space occupied by the cellulose acetate sheet in the column (m 3 ).

[0022] The gold adsorption column of the present disclosure is filled with the above-mentioned cellulose acetate sheet as a filler.

[0023] The gold recovery method disclosed in the present invention comprises: filling the above-mentioned cellulose acetate sheet into a cylindrical container to prepare a filling column; and passing a liquid containing gold ions into the filling column to adsorb the gold ions onto the cellulose acetate sheet.

[0024] The present disclosure may be a method for concentrating a gold solution, which comprises: filling a cylindrical container with the above-mentioned cellulose acetate sheet to prepare a filling column; passing a liquid containing gold ions as a stock solution into the filling column to adsorb the gold ions onto the cellulose acetate sheet; and passing a desorption liquid into the filling column containing the cellulose acetate sheet adsorbed with gold ions to obtain a liquid containing gold ions at a higher concentration than the stock solution.

[0025] Effects of the Invention

[0026] According to the cellulose acetate sheet of the present disclosure, even when it is filled in a column, high liquid permeability can be ensured. According to the column filled with the cellulose acetate sheet of the present disclosure, a large amount of gold-containing solution can be passed in a short time without increasing the internal pressure of the column, thereby efficiently and selectively separating and adsorbing gold. In addition, according to the column, gold ions adsorbed to the cellulose acetate sheet can be easily desorbed by passing a desorption liquid. In addition, since cellulose acetate as a filler is relatively cheap, the gold can be easily recovered in a solid form by incinerating or dissolving the cellulose acetate sheet adsorbed with gold. DETAILED DESCRIPTION

[0027] Hereinafter, an example of a preferred embodiment is specifically described. Each configuration and their combination in each embodiment is an example, and the addition, omission, substitution and other changes of the configuration can be appropriately made without departing from the scope of the present disclosure. The present disclosure is not limited to the embodiment but only to the technical solution. In addition, each scheme disclosed in this specification can also be combined with any other feature disclosed in this specification.

[0028] It should be noted that, in the present specification, "X to Y" indicating a range means "above X and below Y", "ppm" means "mass ppm", and "%" means "mass % (wt.%)". In addition, "mass %" means the so-called mass percentage (weight percent), not the mass concentration (Mass concentration). In the present specification, unless otherwise specified, the test temperature is room temperature (20°C ± 5°C).

[0029] [Cellulose acetate sheet]

[0030] The cellulose acetate sheet of the present disclosure is composed of cellulose acetate having an acetyl substitution degree of 0.80 or more and 2.90 or less, and shows a -1 The average space velocity SV. Cellulose acetate may contain substituents other than acetyl groups within the scope of obtaining the effects of the present disclosure. Here, the average space velocity SV is measured using a column with an inner diameter of 10 mm. Specifically, the column is arranged in a manner such that the axial direction of the column is the vertical direction, and cellulose acetate sheets are filled inside the column so that the height is 2.0 cm. Then, a hydrochloric acid solution with a concentration of 2.0 mol / l (temperature 20°C ± 5°C) is added from the upper surface of the column at a rate of 3.1 ml / min, and is allowed to flow down in the column under atmospheric pressure, and the amount of liquid (m 3 / h) divided by the volume of the space occupied by the cellulose acetate sheet in the column (m 3), and the average space velocity SV is obtained from this. Specifically, the volume is V = 0.005 (m) × 0.005 (m) × π × 0.02 (m) = 1.57 × 10 -6 (m 3 ).

[0031] The cellulose acetate sheet of the present invention can selectively adsorb gold ions in a solution. In the columns used for gold recovery in the past, the phenomenon that molecules with specific ion exchange groups having a chelating effect are firmly bonded to metal ions in an aqueous solution is utilized. In contrast, the adsorption mechanism of the present invention is different from the past, and it is speculated that a part of the molecular structure of the cellulose acetate sheet of the present invention specifically interacts with gold ions, thereby adsorbing gold. More specifically, it is speculated that the size of the pockets (voids) specifically formed by a plurality of cellulose chains is consistent with the size of gold ions, thereby generating a specific physical interaction. In addition, the inventors of the present invention have found that if a cellulose acetate sheet through which a prescribed hydrochloric acid solution can be passed is within a specific range of the above-mentioned average space velocity SV, the contact state with the liquid containing gold ions is improved, and the selective gold adsorption achieved by the above-mentioned physical interaction is more efficiently generated. In addition, in the previous gold recovery column, in the case of desorbing gold firmly bonded to the filler, a special solution containing an acidic component or the like as an extracting solution is required, but according to the present disclosure that adsorbs gold through physical interaction, gold can be easily desorbed using water (pure water) as an extracting solution.

[0032] For example, the surface structure and pocket size of a cellulose acetate sheet vary depending on its manufacturing method and manufacturing conditions. Therefore, in order to obtain a cellulose acetate sheet that produces a specific physical interaction with gold ions and selectively adsorbs gold in a solution, in addition to the particle shape, it is necessary to control various properties such as surface area, pore structure, surface polarity, and particle size distribution. The inventors of the present disclosure have found that these properties of a cellulose acetate sheet are reflected in the average space velocity SV measured under specified conditions. Furthermore, it has been found that by setting the average space velocity SV together with the acetyl substitution degree of cellulose acetate to a specific range, a cellulose acetate sheet that can selectively adsorb and recover gold can be obtained. In other words, the cellulose acetate sheet of the present disclosure has a specific appearance of a sheet, and has a fine shape and physical properties determined by the parameter of the average space velocity SV as an index.

[0033] Moreover, the cellulose acetate sheet of the present disclosure has excellent liquid permeability when filled in a column. By passing a gold-containing solution into the column, gold can be selectively and efficiently recovered. In other words, the cellulose acetate sheet of the present disclosure can be used as a filler for a gold adsorption (recovery) column. According to the gold recovery column of the present disclosure, it is possible to recover only gold by adsorbing and desorbing it with an extremely high selectivity from a solution obtained by dissolving gold-containing materials called urban mines with a metal dissolving solution (aqua regia) or the like. In addition, according to the cellulose acetate sheet of the present disclosure, it is also possible to selectively recover only gold from a hydrochloric acid solution in which a variety of metal ions are dissolved. For example, according to the cellulose acetate sheet of the present disclosure, gold can be selectively recovered even from a solution in which, in addition to gold (Au), several metal elements such as Li, Be, B, Na, Mg, Al, Si, P, K, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, As, Se, Rb, Sr, Y, Zr, Nb, Mo, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Te, Cs, Ba, Hf, Ta, W, Re, Os, Ir, Pt, Ti, Pb, Bi, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and Th coexist. Furthermore, a super-selective gold adsorption column can be obtained which selectively adsorbs gold even when the solution contains 67 kinds of metal elements (Li, Be, B, Na, Mg, Al, Si, P, K, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, As, Se, Rb, Sr, Y, Zr, Nb, Mo, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Te, Cs, Ba, Hf, Ta, W, Re, Os, Ir, Pt, Au, Ti, Pb, Bi, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and Th).

[0034] In addition, the cellulose acetate sheet of the present disclosure can efficiently adsorb gold even in a low concentration region where the gold concentration in the solution is about 5 ppm. Moreover, the cellulose acetate sheet of the present disclosure can preferentially adsorb gold even from a solution in which other metals other than gold are present at a concentration of 200 times or more. Therefore, the cellulose acetate sheet of the present disclosure can be used to recover gold ions from a mixed dilute solution of hydrochloric acid and nitric acid obtained by diluting aqua regia, which is generally used as a metal dissolving solution in urban mines. For example, in exhaust gas catalysts and hard disks of electronic components, a large amount of platinum is contained together with gold, but according to the technology of the present disclosure, only gold with a low content rate can be selectively recovered from these dissolving solutions.

[0035] In the present specification, "sheet" is defined as particles having a flat shape such as flake, plate, or scale. The cellulose acetate sheet of the present disclosure may have various shapes such as circular, elliptical, or polygonal in plan view.

[0036] The width of the cellulose acetate sheet may be 0.1 mm or more and 10 mm or less, and the thickness may be 0.05 mm or more and 0.1 mm or less. In addition, the width of the cellulose acetate sheet may be 0.1 mm or more and 1 mm or less, and the thickness may be 0.05 mm or more and 0.1 mm or less. In addition, the width of the cellulose acetate sheet may be 0.1 mm or more and 0.17 mm or less, and the thickness may be 0.05 mm or more and 0.1 mm or less. The cellulose acetate sheet has a shape in which the width is larger (longer) than the thickness.

[0037] Here, the width of the cellulose acetate sheet is the average diameter (average of the maximum diameter and the minimum diameter) at the plane with the largest area of ​​the flaky particles, and the thickness of the cellulose acetate sheet is the average diameter at the cross section perpendicular to the plane with the largest area of ​​the flaky particles. The width and thickness of the cellulose acetate sheet are obtained by microscopic observation. For example, the width and thickness of 100 flaky particles randomly selected from a SEM image (magnification 10 times) obtained by a scanning electron microscope can be read and the respective average values ​​can be calculated to obtain the width and thickness of the cellulose acetate sheet.

[0038] When the acetyl substitution degree DS of the cellulose acetate constituting the cellulose acetate sheet is 0.80 or more and 2.90 or less, it is preferably 0.90 or more, more preferably 1.00 or more, and further preferably 1.10 or more. In addition, it is preferably 2.80 or less, more preferably 2.70 or less, and further preferably 2.60 or less. The acetyl substitution degree DS is preferably 0.90 or more and 2.80 or less, more preferably 1.00 or more and 2.70 or less, and further preferably 1.10 or more and 2.60 or less. It should be noted that the cellulose acetate may contain other substituents other than the acetyl group within the scope of obtaining the effects of the present disclosure. As such other substituents, acyl groups such as propionyl, butyryl, valeryl, hexanoyl, heptanoyl, octanoyl, nonanoyl, undecanoyl, dodecanoyl, tridecanoyl, tetradecanoyl (myristoyl), pentadecanoyl, hexadecanoyl, heptadecanoyl, and octadecanoyl (stearoyl) can be cited.

[0039] The degree of acetyl substitution DS of cellulose acetate is determined by converting the degree of acetylation AV (%) indicating the amount of bonded acetic acid per unit mass of cellulose using the following formula.

[0040] DS=162.14×AV×0.01 / (60.052-42.037×AV×0.01)

[0041] Here, the acetylation degree AV of cellulose acetate can be measured according to the description of ASTM: D-817-91 (Testing methods for cellulose acetate, etc.). The acetyl substitution degree DS of cellulose acetate can also be measured by 1 It can be determined by H-NMR measurement.

[0042] The average space velocity SV of the cellulose acetate sheet of the present disclosure obtained by the above method exceeds 1.0 h -1 From the perspective of improving gold recovery efficiency, 2.0 h is preferred. -1 More than 10.0h -1 More than 50.0h -1 Above, particularly preferably 80.0h -1 In addition, the average space velocity SV is preferably 120h -1 Below, more preferably 110h -1 The average space velocity SV is preferably more than 1.0h -1 And 120h -1 Below, more preferably 2.0h -1 More than 110 hours -1 Below, more preferably 10.0h -1 More than 110 hours -1 Below, more preferably 50.0h -1 More than 110 hours -1 Below, more preferably 80.0h -1 Above and 108h -1 Below, particularly preferably 85.0h -1 Above and 108h -1 In addition, the average space velocity SV is 85.0h -1 Above and 92.0h -1 The following ranges are also preferred. Note that the details of the method for measuring the average space velocity SV and the measurement conditions are described below through examples.

[0043] Here, "space velocity (SV)" refers to the speed of a liquid passing through a packing in a column, for example, when a liquid is passed through a packed column, and is defined as the inverse of the time that the liquid is in contact with the packing. In this specification, "average space velocity SV" is expressed as the volume flow rate (m / s) of a liquid passing through a packing (i.e., cellulose acetate sheet) packed in a column per unit time under atmospheric pressure. 3 / h) relative to the volume of the packing (m 3). That is, the average space velocity SV is an index of the liquid permeability of the column when the cellulose acetate sheet of the present disclosure is used as a filler of the column, and is an index showing the processing capacity (liquid processing volume) per unit time of the column (for example, a column for gold adsorption (recovery)). Hereinafter, in this specification, the "average space velocity SV" calculated under atmospheric pressure to identify the cellulose acetate of the present disclosure and the "space velocity SV'" under pressure set in the adsorption test described later are used separately.

[0044] As described above, the cellulose acetate sheet of the present disclosure has a flat shape. It is believed that the flat shape can be uniformly filled into the column and form interparticle spaces through which the treatment liquid can easily pass, thereby contributing to the improvement of the average space velocity SV. Moreover, as described above, the particle size distribution, specific surface area, total pore volume, surface polarity, etc. of the cellulose acetate sheet also affect the average space velocity SV. That is, the average space velocity SV in the present disclosure can also be said to be an index that reflects multiple physical properties such as particle size distribution, specific surface area, total pore volume, etc. in addition to the shape and size of the cellulose acetate sheet. The inventors of the present disclosure conducted intensive research and found that by obtaining a velocity of more than 1.0 h at atmospheric pressure, -1 By selecting various physical properties of the cellulose acetate sheet in a balanced manner within the range of the average space velocity SV, the technical problem of the present disclosure can be solved.

[0045] Hereinafter, various desirable physical properties for obtaining the above-mentioned mean space velocity SV will be described in order.

[0046] The particle size distribution of the cellulose acetate sheet was measured using a test sieve specified in JIS Z8801-1: 2006 in accordance with the general rules for sieving test methods described in JIS Z8815. Specifically, a sieve with a mesh size of 20 (841 μm) and a tray were installed in a Ro-tap machine (manufactured by Iida Seisakusho Co., Ltd., tapping: 156 times / min, rolling: 290 times / min), and 100 g of a sample was vibrated for 5 minutes. The ratio of the mass of the sample on the sieve to the total weight (100 g of the sample) was calculated, thereby determining the ratio of particles having a particle size of 850 μm or more. The details of the method and conditions for measuring the particle size distribution will be described below in the Examples.

[0047] In the particle size distribution of the cellulose acetate sheet of the present disclosure, the ratio of particles having a particle size of 850 μm or more may be 10% or more, 50% or more, 60% or more, 70% or more, 80% or more, 85% or more, or 90% or more, and the upper limit thereof is 100%. In the particle size distribution of the cellulose acetate sheet of the present disclosure, the ratio of particles having a particle size of 850 μm or more may be 10% or more and 100% or less, 50% or more and 100% or more, 60% or more and 100% or less, 70% or more and 100% or less, 80% or more and 100% or less, or 90% or more and 100% or less. If there are many particles having a particle size of less than 850 μm, the packing density in the column becomes too large, and the pressure loss during the passage of liquid may increase. In addition, if the ratio of particles having a particle size of 850 μm or more is high, the average space velocity SV can be increased. It should be noted that in order to adjust the particle size distribution of the cellulose acetate sheet of the present disclosure, classification may be performed using a sieve with an appropriate mesh size.

[0048] From the viewpoint of suppressing the increase of pressure loss when the column is passed through, the cumulative 50% particle size (median particle size: D50) based on the mass basis obtained from the particle size distribution of the cellulose acetate sheet of the present disclosure may be 40 mesh or more, 35 mesh or more, or 30 mesh or more. In addition, from the viewpoint of improving the packing density, the cumulative 50% particle size (median particle size: D50) may be 10 mesh or less, 12 mesh or less, or 14 mesh or less. It should be noted that the cumulative 50% particle size based on mass in the present disclosure is defined as the mesh size (mesh) of the sieve when the mass of particles passing through the mesh exceeds 50% of the mass of the entire sample in a sieving test using a sieve specified in JIS Z8801-1:2006.

[0049] The BET specific surface area of ​​the cellulose acetate sheet disclosed herein may be 1.8 m 2 / g or more, can be 2m 2 / g or more, can be 3m 2 / g or more, can be 5m 2 / g or more, can be 7m 2 / g or more, in addition, it can be 25m 2 / g or less, can be 20m 2 / g or less, can be 18m 2 / g or less. In addition, the BET specific surface area is preferably 1.8 m 2 / g or more and 25m 2 / g or less, more preferably 2m 2 / g or more and 20m 2 / g or less, more preferably 3m 2 / g or more and 18m 2 / g or less, more preferably 5m 2 / g or more and 18m 2 / g or less, and more preferably 7m 2 / g or more and 18m 2 The BET specific surface area is measured by the BET method using nitrogen adsorption in accordance with the method described in JIS Z8831. The details of the measurement method and measurement conditions are described below in the Examples.

[0050] Generally, the smaller the particle size of the cellulose acetate sheet, the larger the specific surface area of ​​the cellulose acetate sheet. As described above, the cellulose acetate sheet of the present disclosure adsorbs gold ions by physical interaction, so a large specific surface area is advantageous. However, if the specific surface area is large, the particle size becomes small, and sometimes the liquid permeability decreases.

[0051] The total pore volume of the cellulose acetate sheet of the present disclosure can be 0.005 cm 3 / g or more, can be 0.007cm 3 / g or more, can be 0.009cm 3 / g or more, can be 0.010cm 3 / g or more, and can be 150cm 3 / g or less, can be 10cm 3 / g or less, can be 1.0cm 3 / g or less. The total pore volume is preferably 0.005cm 3 / g or more and 150cm 3 / g or less, more preferably 0.007cm 3 / g or more and 10cm 3 / g or less, more preferably 0.009 cm 3 / g or more and 1.0cm 3 / g or less. The total pore volume is measured by nitrogen adsorption. The details of the measurement method and measurement conditions are described below in the examples.

[0052] The total pore volume of the cellulose acetate sheet is related to the specific surface area and indicates the state of the voids located on the surface of the sheet. It should be noted that the total pore volume in the present disclosure is a physical property different from the cumulative pore volume obtained by mercury intrusion. The so-called cumulative pore volume is usually measured using a mercury intrusion instrument (manufactured by Quantachrome, PoreMaster 60) and the like, and indicates the volume of pores that are large to a certain extent. On the other hand, the total pore volume of the present disclosure is measured by gas adsorption method, and indicates the volume including even finer voids.

[0053] The load displacement of the cellulose acetate sheet of the present disclosure can be 10 mm or less when loaded with 10 N. The load displacement is obtained by filling a 10 ml cylindrical syringe (made of polypropylene, inner diameter 17 mm) with a cellulose sheet to form a filling layer with a height of 50 mm, compressing the filling layer at a compression speed of 10 mm / min using a universal tensile testing machine (trade name "RTG1310" manufactured by A&D Co., Ltd.), measuring the height of the filling layer when loaded with 10 N, and calculating the difference from the height of the filling layer before compression.

[0054] In this specification, the load displacement is an index indicating the hardness of the cellulose acetate sheet. According to the cellulose acetate sheet whose load displacement is less than 10 mm when loaded with 10 N, even when the column is filled with high density and the pressure loss during liquid flow increases, the particles are not easily deformed, and thus the desired liquid permeability can be ensured. From the viewpoint of obtaining high liquid permeability, the load displacement at a load of 10 N can be less than 8 mm, less than 6 mm, less than 4 mm, and the lower limit is 0 mm. The load displacement of the cellulose acetate sheet at a load of 10 N can be greater than 0 mm and less than 10 mm, greater than 0 mm and less than 8 mm, greater than 0 mm and less than 6 mm, or greater than 0 mm and less than 4 mm.

[0055] As long as the effects of the present disclosure can be obtained, the molecular weight and molecular weight distribution of the cellulose acetate constituting the cellulose acetate sheet are not particularly limited. For example, the weight average molecular weight Mw of the cellulose acetate may be 100,000 or more, 150,000 or more, 170,000 or more, or 400,000 or less, 300,000 or less, or 250,000 or less. In addition, the weight average molecular weight Mw of the cellulose acetate is preferably 100,000 or more and 400,000 or less, more preferably 150,000 or more and 300,000 or less, and further preferably 170,000 or more and 250,000 or less.

[0056] The molecular weight distribution Mw / Mn defined by the weight average molecular weight Mw and the number average molecular weight Mn of cellulose acetate is also not particularly limited. For example, the molecular weight distribution Mw / Mn of cellulose acetate may be 2.0 or more, 2.5 or more, 3.0 or more, 6.0 or less, or 5.0 or less. In addition, the molecular weight distribution Mw / Mn is preferably 2.0 or more and 6.0 or less, more preferably 2.5 or more and 5.0 or less, and further preferably 3.0 or more and 5.0 or less.

[0057] The weight average molecular weight Mw, number average molecular weight Mn, and molecular weight distribution Mw / Mn of cellulose acetate were determined by gel permeation chromatography (GPC) under the following measurement conditions.

[0058] Guard column: PolyPore GUARD, size 50×7.5 mm (Agilent Technologies, Inc.).

[0059] Chromatographic column: PolyPore, size: 300×7.5 mm×2 (Agilent Technologies, Inc.).

[0060] Desorption liquid: NMP + 0.1M LiBr.

[0061] Sample concentration: 0.50% w / v.

[0062] Injection volume: 50 μL.

[0063] Column temperature: 55°C.

[0064] Flow rate: 0.5mL / min.

[0065] Detector: RI (differential refractometer).

[0066] Apparatus: HPLC Prominence + analysis program Lab Solutions Ver.5.73 (manufactured by Shimadzu Corporation).

[0067] Standard sample: polymethyl methacrylate (MM-10 set) (Agilent Technologies, Inc.).

[0068] As long as the effects of the present disclosure can be obtained, the 6% viscosity of the cellulose acetate constituting the cellulose acetate sheet is not particularly limited. For example, the 6% viscosity of the cellulose acetate may be 10 mPa·s or more, 50 mPa·s or more, 70 mPa·s or more, 90 mPa·s or more, or 300 mPa·s or less, 200 mPa·s or less, or 150 mPa·s or less. The 6% viscosity of the cellulose acetate constituting the cellulose acetate sheet is preferably 10 mPa·s or more and 300 mPa·s or less, more preferably 50 mPa·s or more and 200 mPa·s or less, and still more preferably 70 mPa·s or more and 150 mPa·s or less.

[0069] The 6% viscosity of cellulose acetate is measured using an Ostwald viscometer. Specifically, 3.00 g of a dry sample is dissolved in a solvent to prepare a solution having a cellulose acetate concentration of 6 wt / vol%. The solution is measured for falling seconds (s) at 25±1°C using an Ostwald viscometer, and the product of the falling seconds and the viscometer count is calculated as the 6% viscosity (mPa·s). It should be noted that the viscometer count is obtained by a known method using a viscometer calibration standard solution.

[0070] As described above with respect to various physical properties that are ideal for obtaining a predetermined average space velocity SV, for example, there is a tendency that a cellulose acetate sheet having a predetermined average space velocity SV is easily obtained if the material has a large particle size, a large dispersion of particle sizes (i.e., a material with non-uniform particle sizes), a large specific surface area, a material with high sheet hardness, and the like. Specifically, in the case of "large particle size", "small (uniform) particle size distribution", "no pores are formed or the pores are small. Or the total pore volume is small", "small specific surface area", "no or few substituents exposed on the particle surface. Or the hydrophobic part (cellulose skeleton) is exposed or the polarity is low", "high hardness", and the like, there is a tendency that the liquid flow rate becomes larger. On the other hand, in the case of "small particle size", "large (non-uniform) particle size distribution", "large specific surface area", "pores are formed or the pores are large. Or the total pore volume is large", "many or high polarity substituents exposed on the particle surface", "low hardness", and the like, there is a tendency that the liquid flow rate becomes smaller.

[0071] However, multiple characteristics such as surface area, pore structure, surface polarity, and particle size distribution vary in a correlated manner and affect liquid permeability. For example, generally, the smaller the particle size of a cellulose acetate sheet, the larger the specific surface area of ​​the cellulose acetate sheet. However, even if the particle size is small, when no pores are formed or the pores are small, the specific surface area may become small as a result. Therefore, in the present disclosure, the cellulose acetate sheet is determined using the average space velocity SV reflecting these characteristic values ​​as an index rather than determining the optimal numerical range for each characteristic. That is, by making the average space velocity SV obtained by a specific method exceed 1.0 h -1 The cellulose acetate sheet of the present invention is obtained by determining the characteristics that change simultaneously and linked, namely, the particle size distribution, the size and shape of the pores, the hydrophilicity / hydrophobicity of the surface, the amount of change during column filling (hardness, clogging ease), and other fine shapes and physical properties.

[0072] [Method for producing cellulose acetate sheet]

[0073] The method for producing a cellulose acetate sheet of the present disclosure includes a step of mixing a slurry (dope) of cellulose acetate having an acetyl substitution degree of 0.80 or more and 2.90 or less with a precipitant. Here, the slurry refers to a reaction solution obtained by using acetic acid as a reaction solvent in a synthesis step of cellulose acetate (including a hydrolysis step of an acetylation step). In other words, the slurry is also an acetic acid solution in which cellulose acetate is dissolved. Therefore, the slurry in the present disclosure can also be obtained by dissolving an existing cellulose acetate sheet in acetic acid. It should be noted that within the scope of obtaining the effects of the present disclosure, cellulose acetate may also contain other substituents other than acetyl groups. As such other substituents, acyl groups such as propionyl, butyryl, valeryl, hexanoyl, heptanoyl, octanoyl, nonanoyl, undecanoyl, dodecanoyl, tridecanoyl, tetradecanoyl (myristoyl), pentadecanoyl, hexadecanoyl, heptadecanoyl and octadecanoyl (stearoyl) can be listed. Furthermore, when the slurry is dried without mixing it with a precipitant, the entire slurry becomes film-like, and thus it is difficult to appropriately obtain the cellulose acetate sheet of the present disclosure.

[0074] The cellulose acetate sheet of the present invention is obtained by contacting the slurry with a poor solvent (precipitant) for cellulose acetate to precipitate cellulose acetate. In addition, the cellulose acetate sheet of the present invention can be obtained by adjusting the precipitation conditions in the step of contacting the slurry with a poor solvent to obtain a precipitate at the end of the cellulose acetate synthesis step. Conventionally, the step of contacting the slurry with a poor solvent to obtain a precipitate at the end of the cellulose acetate synthesis step is known as a method for manufacturing cellulose acetate sheets. However, in the precipitation step achieved by the conditions generally used, the cellulose acetate sheet of the present invention, that is, the cellulose acetate sheet showing the average space velocity SV, cannot be suitably obtained. This is because the uses of the cellulose acetate sheets, that is, cellulose acetate, manufactured in the past are cigarette filters, optical films, extruded products, etc. Among them, when manufacturing cigarette filters and optical films as the main uses, the cellulose acetate sheet is dissolved in an organic solvent and used. Therefore, as a cellulose acetate sheet for these uses, in order to maintain solubility in an organic solvent, a uniform cellulose acetate sheet is preferred. On the other hand, in the case of the present disclosure, as the cellulose acetate sheet showing a predetermined average space velocity SV, a cellulose acetate sheet with a large particle size, a cellulose acetate sheet with a large dispersion of particle sizes (i.e., a cellulose acetate sheet with an uneven particle size), a cellulose acetate sheet with a large specific surface area, a cellulose acetate sheet with a high sheet hardness, and the like are preferred. In order to obtain such a sheet, the following precipitation conditions different from those in the past are desirable. Specifically, as a poor solvent (precipitate) for cellulose acetate, for example, water is used. In the step of mixing a slurry containing cellulose acetate with a precipitant, by adjusting the concentration of cellulose acetate in the reaction solution (slurry), the temperature of the slurry, the temperature of the precipitant (poor solvent), the speed of mixing or dropping the slurry and the precipitant, the stirring time, and the like, a precipitate of a sheet with a large deviation in particle size and a large specific surface area is obtained, and as a result, a sheet composed of cellulose acetate having an acetyl substitution degree of 0.80 or more and 2.90 or less and showing a particle size of more than 1.0 h under predetermined conditions can be obtained. -1 The average space velocity SV of the cellulose acetate sheet.

[0075] In the step of mixing the slurry containing cellulose acetate with the precipitant, the stirrer used may be a twin-screw kneader or a magnetic stirrer. From the viewpoint of easily obtaining a sheet having a predetermined average space velocity SV, the temperature of the slurry and the precipitant before mixing is preferably low, more preferably 40°C or less, further preferably 30°C or less, and particularly preferably 25°C or less. In addition, after mixing the slurry and the precipitant, the precipitation temperature (i.e., the temperature of the mixture of the slurry and the precipitant) is preferably maintained at 40°C or less, more preferably 30°C or less, and further preferably 25°C or less. There is a tendency that the average space velocity SV value of the obtained cellulose acetate sheet becomes smaller as the temperature of the slurry and the precipitant before mixing and the precipitation temperature are higher. For example, if any of the temperature of the slurry and the precipitant before mixing and the precipitation temperature far exceeds 40°C, it is difficult to obtain the sheet of the present embodiment appropriately.

[0076] The method of precipitating cellulose acetate in the slurry is not particularly limited as long as a cellulose acetate sheet showing the average space velocity SV obtained by the above method is obtained. For example, from the viewpoint of easily obtaining a cellulose acetate sheet showing the desired average space velocity SV, it is preferable to slow down the precipitation rate as much as possible. As such a method, for example, a method of continuously dropping a slurry containing cellulose acetate into a precipitant being stirred can be cited. By slowing down the precipitation rate, precipitation is generated not only on the surface of the droplet in contact with the precipitant, but also from the liquid interface between the precipitant and the slurry to the inside of the slurry droplet. Therefore, a sheet having a continuous structure of the slurry and the precipitant from the surface to the inside, a large specific surface area, and a high hardness is obtained.

[0077] When a slurry containing cellulose acetate is continuously dripped into a precipitant being stirred, the concentration of cellulose acetate as the slurry is preferably about 10% by mass. In addition, the stirring speed of the precipitant (poor solvent) is preferably as low as possible. By stirring at a low speed, a sheet with a larger particle size can be suitably obtained. For example, when the stirring speed is 1 to 110 rpm, the cellulose acetate sheet of the present embodiment can be suitably obtained. There is a tendency that the faster the stirring speed, the smaller the average space velocity SV value of the obtained cellulose acetate sheet. In the case of vigorous stirring at a high speed far exceeding 110 rpm, it is difficult to suitably obtain the sheet of the present embodiment. The temperature of the slurry and the precipitant may be 40°C or less, preferably 25°C or less. In the case where the slurry temperature is very high and accompanied by vigorous stirring during high-temperature aging, a sheet with a small particle size and softness (low hardness) is obtained, so it is difficult to suitably obtain the average space velocity SV of the cellulose acetate sheet of the present embodiment. It is preferred that the size of the dripped droplets is large, and further, a continuous dripping method is preferred. It is also possible to add acetic acid to the slurry in advance before dripping to the precipitant to reduce the cellulose acetate concentration in the slurry. Furthermore, dilute acetic acid may be used as a precipitant instead of water.

[0078] The standing time after stopping the stirring is preferably 0 minutes or more than 0 minutes and about 1 hour. When the standing time is about 0 to 1 hour, the cellulose acetate sheet of the present embodiment can be obtained appropriately. There is a tendency that the value of the average space velocity SV of the obtained cellulose acetate sheet increases as the standing time is longer. When the standing time is much longer than 1 hour, it is difficult to obtain the sheet of the present embodiment appropriately.

[0079] In order to obtain a cellulose acetate sheet showing a desired average space velocity SV, it is necessary to slow down the rate at which cellulose acetate in the slurry precipitates beyond the solubility limit as much as possible, and it is necessary to expand the spatial diffusion of the slurry droplets added to the precipitant (poor solvent) as much as possible. As for the cellulose acetate sheet obtained under such conditions, although the particle size is large, the specific surface area and total pore volume are large, and the load displacement described later is small. In addition, by forming through such a process, the surface state of the cellulose acetate sheet can be made more hydrophilic. As a result, a higher average space velocity SV is obtained. The cellulose acetate sheet having such characteristics has the desired average space velocity SV and can selectively and efficiently recover gold ions. It should be noted that in industry, the average space velocity SV of the obtained cellulose acetate sheet can be adjusted by appropriately changing the shape and capacity of the precipitation tank.

[0080] As long as the effects of the present disclosure can be obtained, the type of precipitant is not particularly limited. It can be appropriately selected according to the target acetyl substitution degree. For example, the precipitant can be a poor solvent for cellulose acetate having the acetyl substitution degree, and can be water, dilute acetic acid or a mixture thereof. A preferred precipitant is dilute acetic acid. The concentration of the dilute acetic acid can be 5% by mass or more, or 10% by mass or more, and preferably 15 to 35% by mass. There is a tendency that the value of the average space velocity SV of the obtained cellulose acetate is larger as the concentration of the dilute acetic acid is higher. If the concentration of the dilute acetic acid is much higher than 35% by mass, it is difficult to appropriately obtain the sheet of the present embodiment. The precipitant may contain an organic solvent within the range that does not hinder the effects of the present disclosure, but when the precipitant contains an organic solvent, it is difficult to obtain the specified average space velocity SV. In addition, low-substituted cellulose acetate has a high tendency to precipitate in a powdery state except for the above-mentioned preferred precipitation method and precipitation conditions. Therefore, in order to obtain a low-substituted cellulose acetate sheet, it is necessary to select the precipitation method and precipitation conditions. In order to suitably obtain the cellulose acetate sheet of the present invention, it is important to combine and appropriately adjust the following factors, among others: (1) the temperature of the slurry and the precipitant before mixing and the precipitation temperature; (2) the stirring speed; (3) the standing time after stopping the stirring; and (4) the concentration of the precipitant (particularly dilute acetic acid, etc.).

[0081] As mentioned above, in order to obtain the desired mean space velocity SV, it is preferred to form a method and condition of slow sedimentation rate. Specifically, it is preferred that the method and condition of slurry and precipitation agent are slowly mixed so as to form an adsorption surface of gold ions on the outer surface of the sheet, and to form concavo-convex on the surface of the sheet. In addition, the stirring speed of the preferred slurry and precipitation agent is slow. The slower the stirring speed of the slurry and precipitation agent, the larger the particle size distribution of the obtained sheet. If high-speed stirring is carried out, a sheet with uniform particle size is obtained, so there is a tendency that the value of the mean space velocity SV decreases.

[0082] The slurry containing cellulose acetate having an acetyl substitution degree of 0.80 to 2.90 can be obtained, for example, by the following steps: step (a) of reacting cellulose with acetic anhydride in the presence of an acid catalyst and an acetic acid solvent to produce cellulose acetate; and step (b) of hydrolyzing the produced cellulose acetate to adjust the acetyl substitution degree to 0.80 to 2.90.

[0083] In the step (a) of producing cellulose acetate, cellulose is acetylated by reacting with acetic anhydride in the presence of an acid catalyst and an acetic acid solvent. The cellulose is preferably activated. Examples of the activation treatment include a method of adding acetic acid or acetic acid containing 1 to 10% by mass of sulfuric acid (sulfur-containing acetic acid) to the raw material cellulose in one step or in two steps.

[0084] As the raw cellulose, wood pulp (coniferous wood pulp, hardwood pulp, etc.), cotton linter, etc. can be used. These raw celluloses can be used alone or in combination of two or more. For example, coniferous wood pulp can be used together with cotton linter or hardwood pulp. When wood pulp is used, pulverized pulp pulverized into a cotton-like state by a disk refiner or the like can also be used.

[0085] The α-cellulose content of the raw material cellulose may be, for example, 90% by mass or more, 92% by mass or more, 95% by mass or more, or 97% by mass or more.

[0086] When acetic acid or acetic acid containing 1 to 10% by mass of sulfuric acid (sulfur-containing acetic acid) is added to the raw material cellulose for activation treatment, 10 to 500 parts by mass of acetic acid and / or sulfur-containing acetic acid may be added to 100 parts by mass of the raw material cellulose. Acetic acid or sulfur-containing acetic acid may be added to the raw material cellulose in one step, sulfur-containing acetic acid may be added after a fixed time has passed after the addition of acetic acid, or acetic acid may be added after a fixed time has passed after the addition of sulfur-containing acetic acid. In addition, the activation treatment may be a method in which acetic acid and / or sulfur-containing acetic acid is added to the raw material cellulose and then left to stand at 17 to 40° C. for 0.2 to 48 hours, or a method in which the raw material cellulose is sealed and stirred at 17 to 40° C. for 0.1 to 24 hours.

[0087] As an acid catalyst used in the step of acetylation of cellulose (preferably activated cellulose) to produce cellulose acetate, sulfuric acid is exemplified. For example, acetylation can be performed by adding cellulose to a mixture containing acetic acid, acetic anhydride, and sulfuric acid, or by adding a mixture of acetic acid and acetic anhydride and sulfuric acid to cellulose.

[0088] As the ratio of acetic acid to acetic anhydride in acetylation, acetic anhydride may be 200 to 400 parts by mass relative to 300 to 600 parts by mass of acetic acid, and acetic anhydride may be 240 to 280 parts by mass relative to 350 to 530 parts by mass of acetic acid. In addition, as the ratio of cellulose and the mixture of acetic acid and acetic anhydride in acetylation, the mixture of acetic acid and acetic anhydride may be 500 to 1000 parts by mass relative to 100 parts by mass of cellulose. As the ratio of cellulose to sulfuric acid in acetylation, concentrated sulfuric acid may be 0.5 to 15 parts by mass, 5 to 14 parts by mass, or 7 to 11 parts by mass relative to 100 parts by mass of cellulose. The acetylation reaction of cellulose may also be carried out by stirring for 30 minutes to 36 hours from the time point when the reaction is started at 20 to 55°C.

[0089] In the step (b) of hydrolyzing the produced cellulose acetate to adjust the degree of acetyl substitution to 0.80 or more and 2.90 or less, for example, during the hydrolysis (saponification), a neutralizing agent is added to stop the acetylation reaction, and the neutralizing agent includes: water (including water vapor); dilute acetic acid; or carbonate, acetate, hydroxide or oxide of calcium, magnesium, iron, aluminum or zinc; etc. It should be noted that dilute acetic acid refers to an aqueous solution of 1 to 50% by mass of acetic acid. As the neutralizing agent, magnesium acetate and calcium acetate are preferred.

[0090] The time of the hydrolysis (saponification) reaction (hereinafter referred to as the aging time) is not particularly limited and can be appropriately adjusted according to the target acetyl substitution degree. Here, the aging time refers to the time from the start of adding the neutralizing agent to the end of the hydrolysis (saponification) reaction. If the aging time is extended, the acetyl substitution degree can be reduced.

[0091] The temperature of the hydrolysis (saponification) reaction (hereinafter referred to as aging temperature) is preferably 50 to 100° C., more preferably 70 to 90° C., and is preferably maintained at the temperature for 20 to 120 minutes. Here, the aging temperature refers to the temperature in the reaction system during the aging time.

[0092] By adjusting the conditions of the hydrolysis reaction, a slurry containing cellulose acetate having an acetyl substitution degree of 0.80 or more and 2.90 or less is obtained. By mixing the slurry and a precipitant under the above conditions, a cellulose acetate sheet having the characteristics of the present disclosure is obtained. Here, the slurry containing cellulose acetate refers to a solution obtained by dissolving the cellulose acetate or a mixture containing cellulose acetate in a solvent. The mixture is a reaction mixture obtained by an acetylation reaction or a hydrolysis reaction.

[0093] The slurry containing cellulose acetate having an acetyl substitution degree of 0.80 or more and 2.90 or less may be applied to the step of mixing with a precipitant as the precipitation step of the cellulose acetate sheet described above, and then the precipitated cellulose acetate sheet may be separated and dried. As a method of separating the cellulose acetate sheet, there can be mentioned a method of dehydrating by filtration or centrifugal separation. As a method of drying the separated cellulose acetate sheet, a known method such as air drying at a predetermined temperature and reduced pressure drying can be used. If drying using electromagnetic waves is used in combination, the above-mentioned average spatial velocity SV may be reduced.

[0094] [Column for gold adsorption]

[0095] In the gold adsorption column disclosed in the present invention, a cellulose acetate sheet having an acetyl substitution degree of 0.80 or more and 2.90 or less is filled as a filler. By passing a gold-containing solution through the column, gold ions in the solution are selectively adsorbed on the cellulose acetate sheet. The gold ions can be separated and recovered by collecting the cellulose acetate sheet adsorbed with gold ions and incinerating or dissolving it in a good solvent. In addition, the gold ions can be desorbed by collecting the cellulose acetate sheet adsorbed with gold ions and mixing it with a desorption liquid (e.g., water). It should be noted that the definition of "column" according to JIS K0214 (2013) "Terms for Analytical Chemistry (Chromatographic Part)" is "a tube or capillary filled with a filler that mainly separates sample components", and the "column for gold adsorption" refers to a column filled with a filler having gold adsorption capacity in a cylindrical or cylindrical container having an inner diameter and a length. For example, the gold adsorption column of the present disclosure may be provided with a liquid inlet and a liquid outlet at both ends of a cylindrical or cylindrical container filled with a filler, respectively, and the liquid inlet and liquid outlet are sealed to prevent air from flowing in from outside the column. In the gold adsorption column of this scheme, since the gold-containing solution or the desorption liquid can be passed under pressure, the adjustment of the space velocity SV' described later becomes easy.

[0096] From the viewpoint of improving the gold recovery efficiency, the filling rate of the cellulose acetate sheet in the gold adsorption column may be 10% or more, 15% or more, or 18% or more. In addition, the filling rate may be 40% or less. It should be noted that the filling rate is the ratio of the volume of the space occupied by the filler to the total capacity of the column.

[0097] From the viewpoint of improving the recovery efficiency of gold, the average space velocity SV when a 2.0 mol / l hydrochloric acid solution (temperature 20°C ± 5°C) is passed through the gold adsorption column exceeds 1.0 h -1 That is, it can be 2.0h -1 Above, it can be 10.0h -1 Above, can be 50h -1 Above, can be 80h -1 In addition, from the perspective of suppressing the increase in pressure loss when the column is passed through, the average space velocity SV may be 120 h -1 Below, can also be 110h -1 the following.

[0098] As long as the effects of the present disclosure are obtained, the material and size of the column filled with the cellulose acetate sheet are not particularly limited. For example, as the material of the column, resin, glass, metal, etc. can be appropriately selected. Since the gold-containing solution introduced into the gold recovery column sometimes contains a strong acid such as aqua regia, the material of the column is preferably an acid-resistant resin or glass.

[0099] Considering the packing property of the cellulose acetate sheet, the inner diameter of the column may be 2 mm or more, 5 mm or more, 100 mm or more, or 1000 mm or more. Considering the processing capacity and suppressing the pressure loss during the liquid flow, the length of the column may be 2 mm or more, 20 mm or more, 200 mm or more, or 20000 mm or more.

[0100] [Gold recovery method]

[0101] The gold recovery method of the present invention includes passing a liquid containing gold ions into the above-mentioned gold adsorption column, so that the gold ions in the liquid are adsorbed on the cellulose acetate sheet. In detail, the gold recovery method of the present invention may include: filling a cellulose acetate sheet with an acetyl substitution degree of 0.8 or more and 2.9 or less in a cylindrical container to prepare a filled column; and passing a liquid containing gold ions into the filled column, so that the gold ions are adsorbed on the cellulose acetate sheet.

[0102] As for the direction of liquid flow, for example, in the case of a packed column arranged in a manner that the column axis direction is the vertical direction, it can be from the upper part of the vertical direction or from the lower part. For example, in Japanese Patent Publication No. 2006-192400, a column regeneration method is disclosed in which the liquid flow direction of the stock solution (treated liquid) and the liquid flow direction of the column regeneration liquid are both set to downward flow. However, in this method, it is necessary to flush all the gold ions adsorbed on the cellulose acetate sheet on the upper part of the column downward, so sometimes the efficiency decreases. Therefore, the liquid flow direction can be changed during the adsorption and desorption of gold ions. It should be noted that as long as the effect of the present disclosure can be obtained, the setting direction of the packed column is not limited to the vertical direction, and the packed column can also be set in the horizontal direction.

[0103] From the viewpoint of improving the adsorption efficiency of gold ions on the cellulose acetate sheet in the packed column, the space velocity SV' when the liquid containing gold ions is passed into the packed column exceeds 1.0 h -1 That is, it can be 2.0h -1 Above, it can be 10.0h -1 Above, can be 50h -1 Above, can be 80h -1 In addition, from the perspective of increasing the adsorption amount and suppressing the pressure loss during liquid flow, the space velocity SV can be 120h -1 Below, it can be 110h -1 Below, can be 100h -1 In other words, in the gold recovery method of the present disclosure, it is preferred that the liquid containing gold ions be heated to a temperature that allows the liquid to be recovered for more than 1 h. -1 The liquid is passed into the above-mentioned packed column at a flow rate of a space velocity SV'. For example, a liquid containing gold ions can be conveyed by using a tubular pump connected to the packed column, and the liquid containing gold ions can be passed into the packed column. The space velocity SV' can be adjusted by adjusting the liquid delivery speed of the tubular pump. From the viewpoint of improving the adsorption efficiency, the liquid can be passed at a space velocity SV' exceeding the average space velocity SV of the filled cellulose acetate sheet, but in this case, the pressure applied to the column may be too large. From the viewpoint of suppressing pressure loss, the space velocity SV' during the liquid passing is preferably greater than 1.0h -1 And 120h -1 The following range.

[0104] As a method for separating and recovering the gold ions adsorbed on the cellulose acetate sheet in a solid form, for example, the cellulose acetate sheet adsorbed with the gold ions may be dissolved in a good solvent, and then the insoluble components containing gold may be recovered and dried. Alternatively, the cellulose acetate sheet adsorbed with the gold ions may be incinerated to recover the incineration residue containing gold. That is, the gold recovery method may further include dissolving or incinerating the cellulose acetate sheet adsorbed with the gold ions. If necessary, the insoluble components may be purified by a known purification method or the incineration residue may be incinerated to recover high-purity gold.

[0105] In addition, high-purity gold can also be recovered by a desorption method as needed. For example, a desorption liquid such as water can be added to a packed column after the gold ions are adsorbed, and the gold ions can be desorbed from the cellulose acetate sheet. In addition, a reducing agent or the like can be added to the desorption liquid containing the desorbed gold ions to precipitate them and recover the gold as a solid component. Moreover, by using a small amount of desorption liquid, a gold-containing solution with a higher concentration than the original liquid containing gold particles is obtained. Therefore, gold can also be recovered using a process suitable for a high-concentration solution such as an electrolytic reduction method.

[0106] In other words, the present disclosure relates to a method for concentrating a gold solution. The method for concentrating a gold solution comprises: passing a liquid (stock solution) containing gold ions into the above-mentioned gold adsorption column to adsorb the gold ions in the liquid onto a cellulose acetate sheet, and then passing a desorption liquid to desorb the gold ions adsorbed onto the cellulose acetate sheet to obtain a liquid containing gold ions at a higher concentration than the stock solution. In detail, the method for concentrating a gold solution of the present disclosure comprises: filling a cellulose acetate sheet having an acetyl substitution degree of 0.8 or more and 2.9 or less into a cylindrical container to prepare a filled column; passing a liquid containing gold ions as a stock solution into the filled column to adsorb the gold ions onto the cellulose acetate sheet; and passing a desorption liquid into the filled column containing the cellulose acetate sheet adsorbed with gold ions to obtain a liquid containing gold ions at a higher concentration than the stock solution.

[0107] As a liquid containing gold, for example, a gold-containing solution obtained by collecting gold-containing materials from discarded electronic equipment, etc. and dissolving the gold-containing materials in aqua regia can be cited. That is, the gold recovery method disclosed in the present invention may also include: preparing a liquid containing gold ions by dissolving or extracting gold from the gold-containing material into aqua regia. The above-mentioned gold-containing material usually has a low gold content. The gold-containing solution obtained by dissolving the gold-containing material in aqua regia also has a low gold ion concentration. For such a dilute solution, known methods such as adding a reducing agent and electrolytic reduction are industrially cost-effective and therefore cannot be applied. In contrast, the gold recovery method disclosed in the present invention and the gold solution concentration method can also be appropriately applied to a liquid containing gold ions at a concentration of less than 1000ppm, preferably less than 800ppm, and more preferably less than 500ppm. Moreover, by applying the gold recovery method disclosed in the present invention and the gold solution concentration method, gold can be efficiently adsorbed and recovered even in a low concentration area where the gold ion concentration is about 5ppm. In addition, gold can be preferentially adsorbed and recovered even from a liquid in which other metals other than gold exist at a concentration of 200 times or more. For example, according to the cellulose acetate sheet of the present disclosure, gold can be selectively recovered even from a solution in which, in addition to gold (Au), several metal elements such as Li, Be, B, Na, Mg, Al, Si, P, K, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, As, Se, Rb, Sr, Y, Zr, Nb, Mo, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Te, Cs, Ba, Hf, Ta, W, Re, Os, Ir, Pt, Ti, Pb, Bi, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and Th coexist. Furthermore, the gold recovery method and the gold solution concentration method disclosed in the present invention can be applied to a liquid containing 67 metal elements (Li, Be, B, Na, Mg, Al, Si, P, K, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, As, Se, Rb, Sr, Y, Zr, Nb, Mo, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Te, Cs, Ba, Hf, Ta, W, Re, Os, Ir, Pt, Au, Ti, Pb, Bi, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Th). According to the present invention, gold can be efficiently recovered from discarded electronic parts, processing scraps of decorative items, waste catalysts, etc.

[0108] Example

[0109] Hereinafter, the present disclosure will be specifically described by way of examples, but the technical scope of the present disclosure is not limited by these examples. It should be noted that the test temperature is room temperature unless otherwise specified.

[0110] The acetylation degree AV and acetyl substitution degree DS, weight average molecular weight Mw and 6% viscosity described in the examples and comparative examples described below were measured by the above-mentioned method. Other physical properties were evaluated by the following methods.

[0111] [Morphological observation]

[0112] The external appearance of the Examples and Comparative Examples was confirmed by observation using a scanning electron microscope (E-1030 type Hitachi ion sputtering device manufactured by HITACHI).

[0113] [Particle size: above 20 mesh]

[0114] The sieving test was conducted in accordance with the provisions of JIS Z8801-1:2006. That is, a sieve with a nominal mesh size of 850 μm, a maximum mesh size tolerance of 127 μm, an average mesh size tolerance of 29 μm, a maximum wire diameter of 580 μm, and a minimum wire diameter of 430 μm was used to determine the ratio (%) of particles with a particle size of 850 μm or more. Specifically, JIS test sieves and trays with mesh sizes of 4000 μm (5 mesh), 1700 μm (10 mesh), 1000 μm (16 mesh), 850 μm (20 mesh), and 500 μm (32 mesh) were prepared. First, a sieve with a mesh size of 4000 μm was installed in a Rotap sieve machine (manufactured by Iida Seisakusho Co., Ltd., knocking: 156 times / min, rotation: 290 times / min), 100 g of a sample was put into the sieve, and after vibrating it for 5 minutes, the sample on the tray was collected. The sample is put into a sieve with a mesh size of 1700 μm and sieved under the same conditions. Similarly, after sieving in sequence using sieves with mesh sizes of 1000 μm, 850 μm, and 500 μm, the mass of the sample on each sieve with a mesh size of 4000 μm, 1700 μm, 1000 μm, 850 μm, and 500 μm is measured. The particle size distribution is prepared using the ratio of the mass of the sample on each sieve to the total mass (100 g) provided for the sieving test and the mesh size of each sieve. In this particle size distribution, the total mass of the sample on the sieves with mesh sizes of 4000 μm, 1700 μm, 1000 μm, and 850 μm is obtained, and the ratio (%) relative to the total mass (100 g) is calculated as the ratio of particles with a particle size of 850 μm or more (above 20 mesh). Similarly, a sieving test is carried out using a JIS test sieve with a mesh size of 106 μm (150 mesh), the mass of the sample passing through the sieve is measured, and the ratio (%) relative to the total mass (100 g) is calculated as the ratio of particles with a particle size less than 106 μm (passing 150 mesh).

[0115] [BET specific surface area and total pore volume]

[0116] The BET specific surface area (m 2 / g) and total pore volume (cm 3 / g). The measuring device used was Belsorp max (manufactured by BEL JAPAN INC), and the sample (test piece) was pretreated at 100°C for 60 minutes before the measurement. It should be noted that the sample in the form of a sheet and a powder was measured in an amount of 0.04 g, and the sample in the form of a fiber (cotton) was measured in an amount of 0.2 g.

[0117] [Load displacement]

[0118] The cylindrical syringe (polypropylene, inner diameter 17mm) with a capacity of 10ml is set in a manner that its axial direction is the vertical direction, and the sample is filled to a height of 50mm from the bottom surface of the syringe to form a filling layer. Use a universal tensile testing machine (trade name "RTG1310" made by A&D Company) to compress the filling layer at a compression speed of 10mm / min, and measure the height H1 (mm) of the filling layer when the load is 10N. Calculate the difference H2-H1 between the height H2 (mm) of the filling layer before compression. The average value of the measured values ​​5 times is used as the load displacement (mm).

[0119] [Column characteristics: Measurement of mean space velocity SV by liquid flow test]

[0120] A glass column with a stopcock (manufactured by Asahi Seisakusho, inner diameter 10 mm) was set in a manner such that the column axis direction was the vertical direction with the stopcock fully opened, and about 0.5 g of filler (e.g., cellulose acetate sheet) was naturally dropped from the bottom of the column to a height of 2.0 cm, thereby preparing a filled column. Specifically, the filler was added to the column in about three times, and each time the filler was added, the side of the column was continuously tapped by hand while filling to a height of 2.0 cm from the bottom of the column. A tubular pump ("tubular pump 1973" manufactured by AS ONE) was used to add a hydrochloric acid solution with a concentration of 2.0 mol / l from the upper end of the column at a liquid delivery rate of 3.1 g / min.

[0121] After the tubular pump starts running, collect and weigh the effluents flowing out from the lower end of the column 0-2 minutes, 2-4 minutes and 4-6 minutes after the hydrochloric acid solution with a concentration of 2.0 mol / l reaches the upper end of the column. It should be noted that at a liquid delivery rate of 3.1 g / min, there is no pressure during the liquid flow, and the hydrochloric acid solution flows down the column under atmospheric pressure. The flow rate (g / min) per minute is calculated based on the average value of the three collection amounts. Similarly, the liquid flow rate (m 3 / h), divided by the volume of the space occupied by the filler in the column (m 3 ), and the average space velocity SV (h -1 Here, the volume of the filler V (m 3 ) is measured by column cross-sectional area (m 2 ) and the height of the filler (m). Specifically, V = (0.005 × 0.005 × π) × 0.02 = 1.57 × 10 -6 (m 3 It should be noted that "1.57E-6" in Tables 1 to 4 below refers to the above-mentioned 1.57×10 -6 .

[0122] [Adsorption test and desorption test]

[0123] First, in a hydrochloric acid solution or a hydrochloric acid-nitric acid mixed solution having a concentration (mol / l) shown in Table 5 below, a salt of each metal is dissolved so as to have a concentration (ppm) shown in Table 5 below, to prepare test solutions AE. The above-mentioned metals are gold (Au), platinum (Pt), iron (Fe), zinc (Zn), aluminum (Al), chromium (Cr), copper (Cu), titanium (Ti), lead (Pb), palladium (Pd), nickel (Ni), tin (Sn), and iridium (Ir).

[0124] Next, a packed column was prepared in the same manner as in the above-mentioned flow test. The above-mentioned tube pump was connected to the packed column, and the operating conditions of the pump were adjusted so that the space velocity SV' was 1.0 (h -1 ), and collect the effluent from the packed column 0 to 3 hours after the liquid is passed. It should be noted that in order to maintain the space velocity SV' at 1.0 (h -1 ) and the column was pressurized, and the test solution was passed into the column under the pressurized state. Then, the concentration (ppm) of each metal ion in the collected effluent was measured using an ICP emission spectrometer (Agilent 5110, manufactured by Agilent Technologies).

[0125] The metal ion concentration (ppm) in the effluent was defined as C1, and the metal ion concentration (ppm) in the test solution before passing through the column was defined as C2. The adsorption rate A (%) of each metal was calculated by the following formula.

[0126] A(%)=(C2-C1) / C2×100

[0127] In addition, the amount of the collected effluent is set to N1 (ml), and the amount of gold (Au) adsorbed in the filling column (mg) is calculated based on the concentration C2 (ppm) in the test liquid before passing into the column and the adsorption rate A (%).

[0128] Then, the desorption test was performed by feeding distilled water as the desorption liquid instead of the test liquid. When feeding the desorption liquid, the operating conditions of the pump were adjusted so that the average space velocity SV was 1.0 (h -1 ). The desorption liquid flowing out from the packed column was collected, and the metal ion concentration (ppm) in the desorption liquid was determined by the above method.

[0129] The amount of desorption liquid collected is set as N2 (ml), the metal ion concentration in the desorption liquid is set as C3 (ppm), and the desorption rate B (%) of each metal is calculated according to the following formula using the amount of effluent liquid collected in the adsorption test N1 (ml) and the metal ion concentration in the effluent liquid C1 (ppm).

[0130] B(%)=(C3×N2×0.001) / (C1×N1×0.001)×100

[0131] The results of using test solution A are shown in Tables 6-8 below. The results of using test solution B are shown in Tables 9-11 below. The results of using test solution C are shown in Tables 12-14 below. The results of using test solution D and collecting the effluent from the packed column at 0 to 1 hour, 1 to 2 hours, and 2 to 3 hours after the flow are shown in Table 15 below. When using test solution E and changing the space velocity SV' during the flow to 5.0 h -1 , 10.0h -1 , 20.0h -1 The results obtained by collecting the effluent from the packed column 0 to 0.5 hours after the liquid was passed are shown in the following Table 16.

[0132] [Comparative Example 1]

[0133] As Comparative Example 1, cellulose acetate (trade name "L-50" manufactured by DAICEL Corporation) of Example 1 of Japanese Patent Application Laid-Open No. 2014-109064 (Patent Document 2) was used. The cellulose acetate was in a powdery state, with a degree of substitution of 2.5, a weight average molecular weight (Mw): 200,000, and a molecular weight distribution (Mw / Mn): 5.0. The cellulose acetate of Comparative Example 1 was subjected to a sieving test using a 150-mesh JIS sieve, and all the powders passed through 150 mesh. In addition, the results of measuring the above-mentioned physical properties, conducting a liquid flow test, and conducting an adsorption test are shown in the following table. In the table, the load displacement "<1" means less than 1 mm. In the liquid flow test and adsorption test of Comparative Example 1, the test liquid overflowed from the column immediately after the tube pump started operating, so liquid flow could not be performed.

[0134] [Example 1]

[0135] The cellulose acetate of Comparative Example 1 (trade name "L-50" manufactured by DAICEL, degree of substitution 2.5, weight average molecular weight (Mw): 200000, molecular weight distribution (Mw / Mn): 5.0) was dissolved in acetic acid to prepare 40 ml of a slurry with a concentration of 20 wt%. Next, 120 ml of dilute acetic acid with a concentration of 20 wt% was prepared as a precipitate (precipitate). Using a low-speed stirrer, 40 ml of the slurry was slowly added to the precipitate adjusted to a temperature of 20°C, with stirring at 10 rpm, and stirred for 10 minutes. Then, the stirring was stopped and the mixture was allowed to stand for 40 minutes to allow the cellulose acetate sheet to harden inside. The obtained sheet was washed and dried to obtain the cellulose acetate sheet of Example 1. The results of measuring the above-mentioned physical properties, conducting a liquid flow test and an adsorption test for the obtained cellulose acetate are shown in the following table. It should be noted that, by microscopic observation, it was confirmed that Example 1 was in the shape of a sheet with a width of 0.1-1 mm and a thickness of 0.05-0.1 mm.

[0136] [Examples 2-4]

[0137] Cellulose acetate with a substitution degree of 2.5, 6% and a viscosity of 70 (mPa·s) was dissolved in acetic acid to prepare 40 ml of a slurry with a concentration of 10 wt%. Next, dilute acetic acid with a concentration of 10 wt% was prepared as a precipitation solution (precipitation solution). The slurry was added dropwise from a 200 ml graduated pipette to the precipitation solution adjusted to a temperature of 25°C while stirring at 100 rpm using a magnetic stirrer.

[0138] In Examples 2 and 4, stirring was stopped and the mixture was left to stand for 30 minutes to allow the cellulose acetate sheet to harden to the inside. The obtained sheets were washed and dried to obtain cellulose acetate sheets of Examples 2 and 4. Microscopic observation confirmed that Example 2 had a sheet shape of 0.1-0.17 mm in width and 0.05-0.1 mm in thickness.

[0139] In Example 3, stirring was stopped and the mixture was left for 40 minutes to allow the cellulose acetate sheet to harden inside. The obtained sheet was washed and dried, and then sieved using a JIS sieve. A portion of the sheet with a particle size of 20 mesh was removed, and the mixture was mixed with the sheet with a particle size of 20 mesh so that the ratio of the particle size of 20 mesh was 10 wt %, thereby obtaining the cellulose acetate sheet of Example 3. It should be noted that the amount of the cellulose acetate sheets of Examples 2 to 4 that passed through 150 mesh was less than 1%. In addition, the results of measuring the above-mentioned physical properties, conducting the liquid flow test and the adsorption test are shown in the following table.

[0140] [Comparative Example 2]

[0141] As Comparative Example 2, the fiber bundle-like cellulose acetate of Example 12 of Japanese Patent Application Laid-Open No. 2014-109064 (Patent Document 2) was used. Specifically, a slurry in which cellulose acetate (trade name "L-50" manufactured by DAICEL) was dissolved was used to spin by dry spinning to obtain a cellulose acetate in the form of a long fiber bundle having a single fineness of 0.9 denier and a total fineness of 20,000. It should be noted that since Comparative Example 2 is a long fiber bundle, particle size measurement by sieving cannot be performed. The results of measuring the above-mentioned physical properties, conducting a liquid flow test and an adsorption test are shown in the table below. In Comparative Example 2, liquid flow was performed for several minutes from the start of the operation of the tube pump, but if the operation was continued afterwards, the test liquid overflowed from the column, so the test could not be continued.

[0142] [Examples 5-7]

[0143] The cellulose acetate of Comparative Example 1 (trade name "L-50" manufactured by DAICEL) was dissolved in acetic acid to prepare 40 ml of a slurry with a concentration of 20 wt%. Next, dilute acetic acid with a concentration of 30 wt% was prepared as a precipitate (precipitate). A magnetic stirrer was used to stir at 100 rpm, and all of the slurry was dripped from a 200 ml graduated pipette into the precipitate adjusted to a temperature of 25°C. After stopping the stirring, it was allowed to stand for 40 minutes to allow the cellulose acetate sheet to harden inside. The obtained sheet was washed and dried, and then sieved using a JIS sieve. A portion of the sheet with a particle size of 20 mesh was removed, and the cellulose acetate sheets of Examples 5-7 were obtained by mixing with the sheet with a particle size of 20 mesh so that the ratio of the particle size of 20 mesh was the ratio shown in Table 2 below. The ratio of the sheets with a particle size of 150 mesh was less than 1%. The results obtained by measuring the above-mentioned physical properties, conducting liquid flow tests and adsorption tests are shown in the table below.

[0144] [Example 8]

[0145] The same procedure as in Example 5 was followed except that the standing time after stopping the stirring was changed to 20 minutes to allow the cellulose acetate sheet to precipitate. The obtained sheet was washed and dried, and then pulverized using a Makino type pulverizer (manufactured by Makino Sangyo Co., Ltd., model: DD-2-3.7) to obtain a cellulose acetate sheet of Example 8. The pulverization conditions were set to a rotation speed of 2450 rpm and a screen diameter of 1.30 mm. The percentage of flakes with a particle size of 20 mesh obtained by the JIS sieving test was 19 wt %, and the percentage of flakes with a particle size of 150 mesh was 11 %. The results of measuring the above-mentioned physical properties, conducting the liquid flow test and the adsorption test are shown in the following table.

[0146] [Example 9 and Comparative Example 7]

[0147] 5.1 parts by mass of acetic acid and 2.0 parts by mass of water were added to 1 part by mass of cellulose acetate (manufactured by DAICEL, trade name "L-50"), and the mixture was stirred for 3 hours to dissolve the cellulose acetate. After adding 0.13 parts by mass of sulfuric acid to the solution, the solution temperature was kept at 70°C for hydrolysis in Example 9, and the solution temperature was kept at 95°C for hydrolysis in Comparative Example 7. In order to prevent the precipitation of cellulose acetate during hydrolysis, water was added to the system twice. That is, after 1 hour, 0.67 parts by mass of water was added to the system over 5 minutes. Furthermore, after 3 hours, 1.33 parts by mass of water was added to the system over 10 minutes, and then the reaction was further continued at 70°C for 7 hours in Example 9, and the reaction was further continued at 95°C for 2.5 hours in Comparative Example 7.

[0148] The temperature of the reaction liquid after the hydrolysis was cooled to room temperature (about 25° C.), and 15 parts by weight of a precipitation solvent (methanol) was added to the reaction mixture to generate a precipitate.

[0149] The precipitate was recovered as a wet cake having a solid content of 15 wt%, and washed by adding 8 parts by weight of methanol to remove liquid until the solid content was 15 wt%. This operation was repeated three times. The washed precipitate was further washed twice with 8 parts by weight of methanol containing 0.004 wt% of potassium acetate to neutralize it, and dried to obtain low-substituted cellulose acetate.

[0150] In order to obtain a sheet from the obtained low-substituted cellulose, pyridine was added to prepare a concentrated solution in such a manner that the sheet was 20 wt%. 100 mL of methanol was added to a conical flask. The concentrated pyridine solution and methanol were cooled to a degree where no condensation occurred, and 5 mL of the cooled concentrated pyridine solution was slowly added to the cooled methanol. After the addition, the sheet was stirred with a pressure-proof explosion-proof stirrer to precipitate the sheet. The obtained sheet was washed with water and dried to obtain cellulose acetate sheets of Example 9 and Comparative Example 7. The results obtained by measuring the above-mentioned physical properties, conducting liquid flow tests and adsorption tests are shown in the table below. In the liquid flow tests and adsorption tests of Comparative Example 7 and Example 9, after the tube pump started to operate, the sheet dissolved and liquid could not be passed.

[0151] [Example 10]

[0152] Cellulose acetate (substitution degree 2.50, trade name "L-50" manufactured by DAICEL) was dissolved in acetic acid to prepare 40 ml of a slurry with a concentration of 20 wt%. Next, 120 ml of dilute acetic acid with a concentration of 20 wt% was prepared as a precipitate (precipitate). Using a stirrer at 100 rpm, 40 ml of the slurry was slowly added to the precipitate adjusted to a temperature of 20°C, and stirred for 10 minutes. Then, the stirring was stopped, and the precipitated cellulose acetate sheet was immediately washed with water, filtered and dried, thereby obtaining a cellulose acetate sheet of Example 10. The results of measuring the above-mentioned physical properties, conducting the liquid flow test and the adsorption test are shown in the following table.

[0153] [Comparative Example 3]

[0154] Cellulose acetate sheets were prepared according to Comparative Example 1 of Japanese Patent Application Laid-Open No. 2017-52961. Specifically, pre-hydrolyzed kraft pulp of a broadleaf tree having an α-cellulose content of 98.4 wt% was pulverized into a cotton-like state using a disk refiner. 26.8 parts by weight of acetic acid was sprayed onto 100 parts by weight of the pulverized pulp (water content 8%) in a mist form, stirred sufficiently, and then left to stand for 60 hours for activation as a pretreatment (activation step).

[0155] The activated pulp is added to a mixture consisting of 323 parts by mass of acetic acid, 245 parts by mass of acetic anhydride, and 13.1 parts by mass of sulfuric acid. The mixture is precooled to 5°C. The maximum temperature is adjusted from 5°C to 40°C over 40 minutes, and acetylation is performed for 90 minutes from the time when the pulp is added to the mixture. Then, a neutralizer (24% magnesium acetate aqueous solution) is added over 3 minutes to adjust the amount of sulfuric acid (matured sulfuric acid amount) to 2.5 parts by mass. Further, after the reaction bath is heated to 75°C, water is added to make the concentration of the reaction bath water (matured water) 52 mol%. Mature at 85°C for 100 minutes, and the sulfuric acid is neutralized with magnesium acetate, thereby stopping the aging, and a reaction mixture containing cellulose acetate, i.e., a slurry, is obtained.

[0156] 1200 parts by mass of dilute acetic acid (10 wt%) at 20°C and 400 parts by mass of a reaction mixture containing cellulose acetate (slurry temperature 85°C) were added to a commercial mixer (manufactured by Panasonic, model: MX-152SP-W), and stirred for 4 seconds by the mixer to precipitate. The temperature of the precipitate at this time was about 37°C. The precipitated cellulose acetate was immediately washed with water, filtered out and dried to obtain a cellulose acetate sheet of Comparative Example 3. The results of measuring the above-mentioned physical properties, the liquid flow test and the adsorption test are shown in the following table.

[0157] [Comparative Examples 4 and 6]

[0158] The cellulose acetate sheet was precipitated in the same manner as in Example 5 except that the temperature of the precipitate (precipitate) was adjusted to 30°C and the standing time after stopping the stirring was changed to 20 minutes. The obtained sheet was washed and dried, and then pulverized using a Makino type pulverizer (manufactured by Makino Sangyo Co., Ltd., model: DD-2-3.7) to obtain cellulose acetate sheets of Comparative Examples 4 and 6. The pulverization conditions were set to a rotation speed of 2450 rpm and a screen diameter of 1.5 mm. The pulverization time was adjusted so that the ratio of particles with a size of 20 mesh and particles with a size of 150 mesh obtained by the JIS sieving test was the value shown in Table 3 below. As a result, in Comparative Example 6, the ratio of particles with a size of 20 mesh was 1.9 wt%, and the ratio of particles with a size of 150 mesh was 10%, and in Comparative Example 4, the ratio of particles with a size of 20 mesh was 0.5 wt%, and the ratio of particles with a size of 150 mesh was 15%. The results of measuring the above-mentioned physical properties, conducting the liquid flow test and the adsorption test are shown in the table below.

[0159] [Comparative Example 5]

[0160] In Comparative Example 5, fiber bundle-shaped cellulose acetate of Example 12 of Japanese Patent Application Laid-Open No. 2014-109064 (Patent Document 2) was used in the same manner as in Comparative Example 2. However, the filling amount in the column was changed to 0.01 g during the flow test and the adsorption test. The results of the flow test and the adsorption test performed when the above-mentioned physical properties were measured and the filling amount was set to 0.01 g are shown in the following table.

[0161] [Comparative Example 8]

[0162] In Comparative Example 8, powdered cellulose acetate propionate (acetyl substitution degree 0.07, propyl substitution degree 1.91, total substitution degree 1.98) was used instead of cellulose acetate. The results of measuring the above-mentioned physical properties and conducting the liquid flow test are shown in the following table.

[0163] [Comparative Example 9]

[0164] In Comparative Example 9, a cellulose acetate sheet was prepared according to the manufacturing method of Comparative Example 5 of Japanese Patent Application Publication No. 2017-052961. In the obtained cellulose acetate sheet, the acetylation degree AV was 53.9%, the 6% viscosity was 87 mPa·s, and the ratio of particles with a particle size of 500 μm or more was 99.0 wt%. It should be noted that the slurry temperature (precipitation liquid temperature) was not disclosed in Comparative Example 5 of Japanese Patent Application Publication No. 2017-052961, so a slurry temperature of 60°C was adopted as a technical standard. The basis of 60°C is the description of the slurry temperature of 60 to 80°C in "Cellulose acetate property and application", which is regarded as a textbook of this technology. This Comparative Example 9 was used as a reproduction of Comparative Example 5 of Japanese Patent Application Publication No. 2017-052961, and the results of measuring the above-mentioned physical properties and conducting the liquid flow test are shown in the following table.

[0165] [Comparative Example 10]

[0166] In Comparative Example 10, a cellulose acetate sheet was prepared according to the manufacturing method of Comparative Example 6 of Japanese Patent Application Laid-Open No. 2017-052961. As in Comparative Example 9, the slurry temperature was set to 60°C. The obtained cellulose acetate sheet had an acetylation degree AV of 55.4%, a 6% viscosity of 75 mPa·s, and a ratio of particles having a particle size of 500 μm or more of 98.0 wt%. This Comparative Example 10 was a reproduction of Comparative Example 6 of Japanese Patent Application Laid-Open No. 2017-052961, and the results of measuring the above-mentioned physical properties and conducting a liquid flow test are shown in the following table.

[0167] [Comparative Example 11]

[0168] In Comparative Example 11, the same operation as in Example 4 of International Publication No. 2014 / 142166 was performed to obtain a precipitate. The same operation as in Example 4 of International Publication No. 2014 / 142166 was performed on the precipitate to obtain low-substituted cellulose acetate. The obtained precipitate and low-substituted cellulose acetate were in powder form. The above-mentioned physical properties of the obtained low-substituted cellulose acetate were measured and the results of the liquid flow test are shown in the following table.

[0169] [Comparative Example 12]

[0170] A cellulose acetate sheet was prepared in the same manner as in Example 1 of International Publication No. 2018 / 139319. It should be noted that, as Comparative Example 12, a cellulose acetate sheet that had undergone a pulverization step (paragraph 0104 of International Publication No. 2018 / 139319) and an impregnation step (paragraph 0106 of International Publication No. 2018 / 139319) was used. The obtained cellulose acetate sheet was quite fine as a sheet and was substantially in a powdery state. The results of measuring the above-mentioned physical properties and conducting a liquid flow test are shown in the following table.

[0171] [Comparative Example 13]

[0172] In Comparative Example 13, cellulose acetate was obtained by the same method as in Example 1 of Japanese Patent Application Laid-Open No. 2021-161320. In detail, during hydrolysis, the reaction mixture was transferred to a pressure-resistant container, and 98 parts by weight of warm water at about 90°C was added and mixed. The reaction mixture was irradiated with microwaves (Monowave 100, frequency 2455 MHz) as a heat source from the outside of the pressure-resistant container to heat it, reaching 148°C in 90 minutes and maintaining it at 148°C for 12 minutes (deacylation process). The slurry temperature after the deacylation process was about 100°C, although the atmospheric pressure was released. The 100°C reaction product (slurry) was added to a large amount of dilute acetic acid aqueous solution under vigorous stirring, and the flake cellulose acetate was separated, then fully washed with water and dried to obtain a product. The degree of acetylation of the obtained cellulose acetate was 55.2% (total degree of acetyl substitution was 2.43), and the 6% viscosity was 95 mPa·s. The obtained tablets had fine particle size. The results of measuring the above-mentioned physical properties and conducting a liquid flow test are shown in the following table.

[0173] [Comparative Example 14]

[0174] In Comparative Example 14, cellulose acetate was precipitated in the same manner as in Comparative Example 1 of Japanese Patent Application Laid-Open No. 2018-119052. The precipitated cellulose acetate was washed with water, immersed in a dilute calcium hydroxide aqueous solution (20 ppm), filtered out, dried, and pulverized using a Makino type pulverizer (manufactured by Makino Sangyo Co., Ltd., model: DD-2-3.7). The pulverization conditions were set to a rotation speed of 2450 rpm and a screen diameter of 1.5 mm. The obtained product was powdered cellulose acetate, with an acetylation degree AV of 55.8% and a 6% viscosity of 110 mPa·s. The results of measuring the above-mentioned physical properties and conducting a liquid flow test are shown in the following table.

[0175] [Table 1]

[0176] Table 1 (Physical properties)

[0177]

[0178] [Table 2]

[0179] Table 2 (Physical properties)

[0180]

[0181]

[0182] [Table 3]

[0183] Table 3 (Physical properties)

[0184]

[0185] [Table 4]

[0186] Table 4 (Physical properties)

[0187]

[0188]

[0189] [Table 5]

[0190] (Table 5) Test solution

[0191]

[0192] [Table 6]

[0193] (Table 6) Test solution A

[0194]

[0195]

[0196] [Table 7]

[0197] (Table 7) Test solution A

[0198]

[0199]

[0200] [Table 8]

[0201] (Table 8) Test solution A

[0202]

[0203] [Table 9]

[0204] (Table 9) Test solution B

[0205]

[0206] [Table 10]

[0207] (Table 10) Test solution B

[0208]

[0209] [Table 11]

[0210] (Table 11) Test solution B

[0211]

[0212] [Table 12]

[0213] (Table 12) Test solution C

[0214]

[0215] [Table 13]

[0216] (Table 13) Test solution C

[0217]

[0218] [Table 14]

[0219] (Table 14) Test solution C

[0220]

[0221] [Table 15]

[0222] (Table 15) Test solution D

[0223]

[0224]

[0225] [Table 16]

[0226] (Table 16) Test solution E

[0227]

[0228] In Table 1-2, when comparing Example 5-7 in which only the particle size distribution was changed by sieving, there is a tendency that when the particle size is small (the content of the particle size (20 mesh or more) is small), the BET specific surface area becomes large, and as a result, the average space velocity SV becomes slow (the SV value becomes small). In Example 10 obtained using the same cellulose acetate as Example 5-7 as a raw material, the BET specific surface area is larger than that of Example 5-7, but the average space velocity SV becomes larger. It is considered that this is because although the total pore volume is large and the BET specific surface area is large, the particle size is large (the content of the particle size (20 mesh or more) is large), the load displacement is high (hard), and as a result of increasing the space between particles, a large average space velocity SV is obtained.

[0229] When comparing Example 5 with Example 8, the particle size of Example 8 after the pulverization treatment is small (the content of particle size (above 20 mesh) is small, and the particle size (through 150 mesh) is large), and the BET specific surface area is large, but the average space velocity SV becomes large. This is considered to be because the hydrophobic part (skeleton) of cellulose is exposed to the particle surface due to pulverization.

[0230] When Example 1 and Example 6 are compared, the result is that the particle size distribution (particle size (20 mesh or more) and particle size (through 150 mesh)) are the same and the BET specific surface area is also similar, but the average space velocity SV is greatly different. It is considered that the cellulose acetate sheet of Example 6 is obtained under precipitation conditions different from those of Example 1, so the hydrophilic functional groups are exposed to the particle surface more than that of Example 1, resulting in a decrease in the average space velocity SV.

[0231] As shown in Table 4, the expected average space velocity SV was not obtained in Comparative Examples 8 to 14. The reason for this is that since Comparative Example 8 was in a powdery state, the interparticle space was reduced when filled in a column. In Comparative Examples 9 and 10, a precipitant was mixed into a reaction mixture containing cellulose acetate at a high temperature of 60° C., which is a technical standard, using a twin-screw kneader, so that a very soft cellulose acetate sheet was obtained. As a result, the sheet was deformed, the interparticle space was reduced, and the cellulose acetate sheet of the present disclosure could not be obtained. It is considered that in Comparative Examples 12 and 14, which also used a twin-screw kneader, a powdery product was obtained instead of the expected sheet-shaped product. Comparative Example 11 is a low-substituted cellulose acetate, which cannot be precipitated in a sheet form.

[0232] It is considered that in Comparative Example 13, a dilute aqueous acetic acid solution (precipitant) was added to the reaction product containing cellulose acetate under vigorous stirring to separate the cellulose acetate, so the precipitation rate was fast, and further, the spatial diffusion caused by the droplets of the slurry (reaction product) in the precipitant could not be increased, so the desired average spatial velocity SV could not be obtained.

[0233] As shown in Tables 1-4 and 6-16, the cellulose acetate sheets of the examples were superior in liquid permeability compared to the comparative examples. In addition, it was confirmed that gold could be selectively and efficiently recovered from a solution containing a plurality of metals by using the cellulose acetate sheets of the examples as a column filled with the filler. In addition, by desorption using water, a gold-containing solution having a higher concentration than the original (pre-treatment) gold-containing solution could be obtained. According to the evaluation results, the advantages of the present disclosure are obvious.

[0234] [Public Project]

[0235] The following preferred embodiments of each item are disclosed.

[0236] [Project 1]

[0237] A cellulose acetate sheet having an acetyl substitution degree of 0.80 or more and 2.90 or less and an average space velocity SV determined by the following method exceeding 1.0 h -1 And 120h -1 the following.

[0238] (The above average space velocity SV is obtained by placing a column (inner diameter 10 mm) filled with cellulose acetate sheets at a height of 2.0 cm from the bottom in a vertical direction, injecting a 2.0 mol / l hydrochloric acid solution (temperature 20°C ± 5°C) from the upper surface of the column, causing it to flow down in the column under atmospheric pressure, and calculating the amount of liquid (m 3 / h) divided by the volume of the space occupied by the cellulose acetate sheet in the column (m 3 )).

[0239] [Project 2]

[0240] The cellulose acetate sheet according to item 1, wherein the BET specific surface area is 1.8 m 2 / g or more and 25m 2 / g or less.

[0241] [Item 3]

[0242] The cellulose acetate sheet according to item 1 or 2, wherein the total pore volume is 0.005 cm 3 / g or more and 150cm 3 / g or less.

[0243] [Item 4]

[0244] The cellulose acetate sheet according to any one of items 1 to 3, wherein the ratio of particles having a particle size of 850 μm or more in a particle size distribution determined using a JIS test sieve is 50% or more.

[0245] [Item 5]

[0246] The cellulose acetate sheet according to any one of items 1 to 4, wherein a load displacement measured by the following method is 10 mm or less.

[0247] (The above load displacement is obtained by the following method: a 10 ml cylindrical syringe (made of polypropylene, inner diameter 17 mm) is filled with cellulose acetate sheets to form a filling layer with a height of 50 mm, and the filling layer is compressed at a compression speed of 10 mm / min using a universal tensile testing machine (trade name "RTG1310" manufactured by A&D Co., Ltd.), and the height of the filling layer is measured when the load is 10 N, and the difference between the height of the filling layer and the height before compression is calculated).

[0248] [Item 6]

[0249] The cellulose acetate sheet according to any one of items 1 to 5, wherein the cellulose acetate sheet is a filler for a column for gold adsorption.

[0250] [Item 7]

[0251] A column for gold adsorption, the column for gold adsorption being filled with the cellulose acetate sheet as described in any one of items 1 to 6 as a filler.

[0252] [Item 8]

[0253] The gold adsorption column according to Item 7, wherein the filling rate of the cellulose acetate sheet is 10% or more.

[0254] [Item 9]

[0255] A method for recovering gold, comprising passing a liquid containing gold ions into the gold adsorption column as described in item 7 or 8, so that the gold ions in the liquid are adsorbed on the above-mentioned cellulose acetate sheet.

[0256] [Item 10]

[0257] A method for recovering gold, comprising: filling a cylindrical container with a cellulose acetate sheet as described in any one of items 1 to 6 to form a filled column; and passing a liquid containing gold ions into the filled column to adsorb the gold ions onto the cellulose acetate sheet.

[0258] [Item 11]

[0259] The method for recovering gold according to item 10, wherein the liquid containing gold ions is made to be able to obtain more than 1.0h -1 The flow rate of the space velocity SV' is passed into the above-mentioned packed column.

[0260] [Item 12]

[0261] The gold recovery method according to item 10 or 11, wherein the gold recovery method further comprises: dissolving or incinerating the cellulose acetate sheet adsorbed with gold ions.

[0262] [Item 13]

[0263] The method for recovering gold according to any one of items 10 to 12, wherein the method for recovering gold further comprises: preparing the liquid containing gold ions by dissolving or extracting gold from the gold-containing material into aqua regia.

[0264] [Item 14]

[0265] A method for concentrating a gold solution, the method comprising: filling a cylindrical container with a cellulose acetate sheet as described in any one of items 1 to 6 to prepare a filled column; passing a liquid containing gold ions as a stock solution into the filled column to adsorb the gold ions onto the cellulose acetate sheet; and passing a desorption liquid into the filled column containing the cellulose acetate sheet adsorbed with gold ions to obtain a liquid containing gold ions at a higher concentration than that of the stock solution.

[0266] [Item 15]

[0267] A method for producing a cellulose acetate sheet according to any one of items 1 to 6, comprising the step of mixing a slurry containing cellulose acetate having an acetyl substitution degree of 0.80 or more and 2.90 or less with a precipitant,

[0268] The temperature of the slurry and the precipitant during the mixing is 40°C or less.

[0269] [Item 16]

[0270] A use of a cellulose acetate sheet in the manufacture of a packed column, wherein the use of the cellulose acetate sheet in the manufacture of a packed column is the use of the cellulose acetate sheet as described in any one of items 1 to 6, wherein the use of the cellulose acetate sheet is the use of the cellulose acetate sheet in the manufacture of a packed column filled with the cellulose acetate sheet, wherein a liquid containing gold ions is passed as a stock solution into the packed column to adsorb the gold ions onto the cellulose acetate sheet.

[0271] [Item 17]

[0272] A use of a cellulose acetate sheet in the manufacture of a packed column, wherein the use of the cellulose acetate sheet in the manufacture of a packed column is the use of the cellulose acetate sheet as described in any one of items 1 to 6, wherein the use of the cellulose acetate sheet is the use of the cellulose acetate sheet in the manufacture of a packed column filled with the cellulose acetate sheet, wherein a liquid containing a plurality of metal ions is passed as a stock solution into the packed column, thereby selectively adsorbing gold ions to the cellulose acetate sheet.

[0273] [Item 18]

[0274] Use of the cellulose acetate sheet according to item 16 or 17 in the manufacture of a packed column, wherein a desorption solution containing gold ions at a higher concentration than the above-mentioned stock solution is obtained by passing a desorption solution through a packed column containing the above-mentioned cellulose acetate sheet adsorbed with gold ions.

[0275] [Item 19]

[0276] The cellulose acetate sheet according to any one of items 1 to 6, wherein the average space velocity SV is 2.0 h -1 More than 110 hours -1 the following.

[0277] [Item 20]

[0278] The cellulose acetate sheet according to any one of items 1 to 6 and 19, wherein the average space velocity SV is 10.0 h -1 More than 110 hours -1 the following.

[0279] [Item 21]

[0280] The cellulose acetate sheet according to any one of items 1 to 6 and items 19 to 20, wherein the average space velocity SV is 50.0 h -1 More than 110 hours -1 the following.

[0281] [Item 22]

[0282] The cellulose acetate sheet according to any one of items 1 to 6 and items 19 to 21, wherein the average space velocity SV is 80.0 h -1 Above and 108h -1 the following.

[0283] [Item 23]

[0284] The cellulose acetate sheet according to any one of items 1 to 6 and items 19 to 22, wherein the average space velocity SV is 85.0 h -1 Above and 108h -1 the following.

[0285] [Item 24]

[0286] The cellulose acetate sheet according to any one of items 1 to 6 and items 19 to 23, wherein the average space velocity SV is 85.0 h -1 Above and 92.0h -1 the following.

[0287] [Item 25]

[0288] The cellulose acetate sheet according to any one of items 1 to 6 and items 19 to 24, wherein the BET specific surface area is 7 m 2 / g or more and 18m 2 / g or less.

[0289] [Item 26]

[0290] The cellulose acetate sheet according to any one of items 1 to 6 and items 19 to 25, wherein the total pore volume is 0.009 cm 3 / g or more and 1.0cm 3 / g or less.

[0291] [Item 27]

[0292] The cellulose acetate sheet according to any one of items 1 to 6 and 19 to 26, wherein Mw is 170,000 to 250,000.

[0293] [Item 28]

[0294] The cellulose acetate sheet according to any one of items 1 to 6 and 19 to 27, wherein the 6% viscosity of cellulose acetate constituting the cellulose acetate sheet is 70 mPa·s or more and 150 mPa·s or less.

[0295] [Item 29]

[0296] The cellulose acetate sheet according to any one of Items 1 to 6 and Items 19 to 28, wherein the acetyl substitution degree DS is 1.10 or more and 2.60 or less.

[0297] [Item 30]

[0298] The cellulose acetate sheet according to any one of items 1 to 6 and 19 to 29, wherein the cellulose acetate sheet has a width of 0.1 mm to 1 mm, and a thickness of 0.05 mm to 0.1 mm.

[0299] [Item 31]

[0300] The cellulose acetate sheet according to any one of items 1 to 6 and 19 to 30, wherein the cellulose acetate sheet has a shape in which the width is longer than the thickness.

[0301] [Item 32]

[0302] The cellulose acetate sheet according to any one of items 1 to 6 and items 19 to 31, wherein in the particle size distribution of the cellulose acetate sheet, the ratio of particles having a particle size of 850 μm or more is 10% to 100%.

[0303] [Item 33]

[0304] The cellulose acetate sheet according to any one of Items 1 to 6 and Items 19 to 32, wherein a load displacement measured by the following method is 0 mm or more and 6 mm or less.

[0305] (The above load displacement is obtained by the following method: a 10 ml cylindrical syringe (made of polypropylene, inner diameter 17 mm) is filled with cellulose acetate sheets to form a filling layer with a height of 50 mm, and the filling layer is compressed at a compression speed of 10 mm / min using a universal tensile testing machine (trade name "RTG1310" manufactured by A&D Co., Ltd.), and the height of the filling layer is measured when the load is 10 N, and the difference between the height of the filling layer and the height before compression is calculated).

[0306] [Item 34]

[0307] A cellulose acetate sheet having a width of 0.1 mm or more and 1 mm or less and a thickness of 0.05 mm or more and 0.1 mm or less, wherein the width of the cellulose acetate sheet is longer than the thickness, wherein in the particle size distribution of the cellulose acetate sheet, the ratio of particles having a particle size of 850 μm or more is 10% or more and 100% or less, and a BET specific surface area of ​​7 m 2 / g or more and 18m 2 / g or less, with a total pore volume of 0.009cm 3 / g or more and 1.0cm 3 / g or less, Mw is 170000 or more and 250000 or less, and the acetyl substitution degree DS is 1.10 or more and 2.60 or less.

Claims

1. A cellulose acetate sheet having an acetyl substitution degree of 0.80 or more and 2.90 or less, and an average space velocity SV determined by the following method exceeding 1.0 h -1 And 120h -1 the following, The average space velocity SV is obtained by placing a column filled with cellulose acetate sheets at a height of 2.0 cm from the bottom in a vertical direction, injecting a hydrochloric acid solution with a concentration of 2.0 mol / l from the upper surface of the column, causing it to flow down in the column under atmospheric pressure, and dividing the amount of liquid flowing out from the lower surface per unit time by the volume of the space occupied by the cellulose acetate sheets in the column. in, The inner diameter of the column is 10 mm, the temperature of the hydrochloric acid solution is 20°C ± 5°C, and the unit of liquid volume is m 3 / h, the unit of volume is m 3 .

2. The cellulose acetate sheet according to claim 1, in, The BET specific surface area of ​​the cellulose acetate sheet is 1.8 m 2 / g or more and 25m 2 / g or less.

3. The cellulose acetate sheet according to claim 1 or 2, in, The total pore volume of the cellulose acetate sheet is 0.005 cm 3 / g or more and 150cm 3 / g or less.

4. The cellulose acetate sheet according to any one of claims 1 to 3, in, In the particle size distribution determined using a Japanese Industrial Standard test sieve, the ratio of particles having a particle size of 850 μm or more is 50% or more.

5. The cellulose acetate sheet according to any one of claims 1 to 4, in, The load displacement measured by the following method is less than 10 mm. The load displacement is obtained by the following method: a cellulose acetate sheet is filled into a cylindrical syringe with a capacity of 10 ml to form a filling layer with a height of 50 mm, the filling layer is compressed at a compression speed of 10 mm / min using a universal tensile testing machine, the height of the filling layer when the load is 10 N is measured, and the difference between the height of the filling layer and the height before compression is calculated, wherein the cylindrical syringe is made of polypropylene and has an inner diameter of 17 mm, and the universal tensile testing machine is a product name RTG1310 manufactured by A&D Company.

6. The cellulose acetate sheet according to any one of claims 1 to 5, in, The cellulose acetate sheet is a filler for a gold adsorption column. 7 . A column for gold adsorption, the column being filled with the cellulose acetate sheet according to claim 1 as a filler.

8. The gold adsorption column according to claim 7, in, The filling rate of the cellulose acetate sheet is 10% or more.

9. A method for recovering gold, comprising passing a liquid containing gold ions into the gold adsorption column according to claim 7 or 8, so that the gold ions in the liquid are adsorbed onto the cellulose acetate sheet.

10. A method for recovering gold, the method for recovering gold include: Filling a cylindrical container with the cellulose acetate sheet according to any one of claims 1 to 6 to prepare a filled column; as well as A liquid containing gold ions is introduced into the packed column to allow the gold ions to be adsorbed onto the cellulose acetate sheet.

11. The method for recovering gold according to claim 10, in, The liquid containing gold ions is allowed to be heated to a temperature of more than 1.0 h. -1 A flow rate of a space velocity SV' is passed into the packed column.

12. The method for recovering gold according to claim 10 or 11, in, The gold recovery method also includes: The cellulose acetate sheet adsorbed with gold ions is dissolved or incinerated.

13. The method for recovering gold according to any one of claims 10 to 12, in, The gold recovery method also includes: The liquid containing gold ions is prepared by dissolving or extracting gold from a gold-containing material into aqua regia.

14. A method for concentrating a gold solution, the method for concentrating a gold solution include: Filling a cylindrical container with the cellulose acetate sheet according to any one of claims 1 to 6 to prepare a filled column; Passing a liquid containing gold ions as a stock solution into the packed column to allow the gold ions to be adsorbed on the cellulose acetate sheet; and A desorption solution is passed through the packed column containing the cellulose acetate sheet adsorbed with gold ions to obtain a solution containing gold ions at a higher concentration than the original solution.

Citation Information

Patent Citations

  • Small globular ion-exchange resin and manufacture thereof and method for separating rare metal ion

    JP1989111453A

  • Ion-exchange tower

    JP2006192400A

  • Metal recovery method

    JP2014109064A

  • Cellulose acetate powder and manufacturing method of cellulose acetate powder

    JP2017052961A

  • Method for producing cellulose acetate flake

    JP2018119052A